2021
DOI: 10.1111/cas.15157
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of MYD88 via RNA‐controlling CNOT4 and EXOSC3 in colonic mucosa impacts generation of colonic cancer

Abstract: In 2020, the worldwide incidence and mortality of colorectal cancer (CRC) were third and second, respectively. As the 5‐y survival rate is low when CRC is diagnosed at an advanced stage, a reliable method to predict CRC susceptibility is important for preventing the onset and development and improving the prognosis of CRC. Therefore, we focused on the normal colonic mucosa to investigate changes in gene expression that may induce subsequent genetic alterations that induce malignant transformation. Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“… 0.02103 [ 37 ] LUSC EXOSC3 In inflamed mucosa, EXOSC3 and CNOT4-mediated RNA stabilization, including that of MYD88, may trigger cancer development and could serve as potential predictive markers and innovative therapies to control cancer progression. 0.00055 [ 57 ] KRR1 Tumor-associated antigens KRR1 and ZRF1 and their cognate autoantibodies may be considered as potential molecular markers for breast cancer. 0.0318 [ 58 ] LUAD ATP6V0B miRNA-15a, which could regulate ATPase, H(+) transporting, lysosomal21 kDa, V0 subunit b(ATP6V0B), and miRNA-155, were found to be the most significant.…”
Section: Table A1mentioning
confidence: 99%
“… 0.02103 [ 37 ] LUSC EXOSC3 In inflamed mucosa, EXOSC3 and CNOT4-mediated RNA stabilization, including that of MYD88, may trigger cancer development and could serve as potential predictive markers and innovative therapies to control cancer progression. 0.00055 [ 57 ] KRR1 Tumor-associated antigens KRR1 and ZRF1 and their cognate autoantibodies may be considered as potential molecular markers for breast cancer. 0.0318 [ 58 ] LUAD ATP6V0B miRNA-15a, which could regulate ATPase, H(+) transporting, lysosomal21 kDa, V0 subunit b(ATP6V0B), and miRNA-155, were found to be the most significant.…”
Section: Table A1mentioning
confidence: 99%
“…It has been reported that EXOSC1 could cleave single-stranded DNA and sensitize human kidney renal clear cell carcinoma cells to poly (ADP-ribose) polymerase inhibitors [ 11 ]. Additionally, the enhancing expression of EXOSC2 directly regulated by tRNAGluUUC is closely related to breast cancer metastasis [ 12 ], while EXOSC3 and EXOSC4 can trigger the development of colonic and colorectal cancer, respectively [ 13 , 14 ]. Similarly, EXOSC5, EXOSC8, EXOSC9 and EXOSC10 are also remarkably involved in the progression of various cancers, but there is no evidence to show the association between EXOSC6/7 and cancers at present.…”
Section: Introductionmentioning
confidence: 99%